STUDY OF GEOCHEMISTRY AND ROCK MAGNETISM ON RIVER SURFACE SEDI MENTS AROUND LAKE TOWUTI FOR IDENTIFICATION OF MG ANOMALIES IN LAKE TOWUTI - Jannatul Fajar, Silvia
Lake sediments have the potential to store information regarding the history of climate change and the environment in the past, better known as the "paleoclimate." Lake Towuti is one of the lakes in the Malili Lakes System (MLS), south Sulawesi, Indonesia, with an area of 561 km2 and a depth of 203 m. Apart from Lake Towuti, in MLS there are two other large lakes, namely Lake Matano and Lake Mahalona, which are interconnected by the Mahalona River, as well as two satellite lakes (Lake Lontoa and Lake Masapi). Geologically, Lake Towuti is located in the East Sulawesi Ophiolite (ESO) belt, which is dominated by ultramafic rocks. This causes the Towuti Lake sediments to have quite interesting magnetic characteristics because weathering of ultramafic rocks produces lateritic soils. Lateritic soils are soils that have high concentrations of iron (Fe) and aluminum (Al). In addition, Lake Towuti is also located in the center of the Indo-Pacific Warm Pool (IPWP) zone, which is one of the three largest convection zones in the world. so that the Towuti Lake sediments are studied intensively in the reconstruction of climate change and the environment in the past. Based on the results of the study, there are questions regarding the source of the high levels of magnesium (Mg) and calcium (Ca) in the northern part of Lake Towuti, to be precise, at the mouth of the Mahalona river. This is thought to have originated from Lake Mahalona sediments, which were transported via the Mahalona River to Lake Towuti. However, in the Mahalona River, there are river branches (namely the Lampenisu River), which can also contribute to the high Mg and Ca elements. In this study, the sources of Mg and Ca elements were studied by analyzing surface sediment samples from the Lampenisu (LR) and Mahalona (MR) rivers, as well as the combination of the two rivers before entering Towuti Lake. There were twelve samples of surface sediments in this study that would be analyzed magnetically, especially for magnetic susceptibility parameters and magnetic hysteresis, geochemical analysis (X-Ray Fluorescence, XRF), and mineralogical analysis (X-Ray Diffraction, XRD), especially for magnetic minerals. The results of magnetic susceptibility measurements show that the LR sample has a higher magnetic susceptibility ((518.8 ± 27.8) × 10?8 m3/kg) than the MR sample ((218.3 ± 104.4) × 10?8 m3 /kg) and the LR sample also has a lower frequency dependent susceptibility (1.40 ± 0.86%) than the MR sample (4.94 ± 2.23%). However, magnetic domain analysis and magnetic mineral grain size using magnetic hysteresis parameters identified the LR and MR surfaceiv sediment samples as having a Pseudo-single Domain (PSD). Geochemical analysis (XRF) showed that the LR surface sediment samples had elemental concentrations of Mg 13.28 ± 1.68% and Ca 0.89 ± 0.25% which were higher than the MR samples, which only had elemental Mg concentrations of 3.45 ± 1 .59% and Ca 0.66 ± 0.40%. XRD analysis found minerals with a sodalite crystal structure in LR but not in MR. The sodalite mineral is non-magnetic, so the mineral that has the crystal form of sodalite is thought to be a valleyite mineral, a mineral with the chemical formula Ca4(Fe, Al)6O13. The presence of this mineral contributes to the high concentration of elemental Ca in the LR samples. while the high concentration of Mg in LR might be caused by serpentinized peridotite rocks. Thus, LR is considered a source of high levels of Mg and Ca in the northern part of Lake Towuti. This study shows the importance of identifying sediment sources in large lakes such as Lake Towuti, where influx can originate from several rivers around the lake.